Sustainable supply chains – Managing environmental impact data on product platforms - Helo, Petri; Mayanti, Bening; Bejarano, Ronal; Sundman, Christian (Elsevier, 2024)
This paper addresses the importance of sustainable supply chains driven by environmental concerns in various industries. Life cycle assessment (LCA) presents a crucial tool for evaluating environmental impacts, but its case-by-case approach is costly and time-consuming. We present a product platform level solution to capture key supply chain elements and calculate emissions for each product variant using a product configuration system. The study presents a proof-of-concept implementation of a specialized software solution for generating combined greenhouse gas certificates and certificates of origin for product families. A case study on a ship engine demonstrates the solution capabilities, utilizing empirical data from a collaborative effort from an industrial company. The proposed solution is a demonstration of impact quantification for the product platform of a ship engine. In terms of the applicability of the software, a set of scenarios is presented to demonstrate decision-making parameters related to energy sources in operations and transportation modes related to supplier locations. The developed software shows the possibilities of the proposed approach to maintain authenticated environmental impact within the supply chain on a product platform level. The approach integrates the supplier and promotes transparency.
Keywords: Sustainable supply chains; Product platforms; Greenhouse gas emissions; Life cycle assessment; fi=Tuotantotalous|en=Industrial Management|